Stimuli-responsive injectable chitosan-based hydrogels for controlled drug delivery systems - Garshasbi, Hamidreza; Salehi, Saba; Naghib, Seyed Morteza; Ghorbanzadeh, Sadegh; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
In the last decade, injectable hydrogels have attracted a lot of attention due to their excellent functional properties in the field of drug delivery for precise, non-invasive and focused tissue locations. Therefore, designing drug delivery systems (DDS) responsive to hydrogel stimuli to release a drug to an external stimulus with various advantages, can be very challenging. Due to their biocompatibility, mucosal adhesion, and hemostatic activity, chitosan (CS)-based hydrogels offer a lot of potential for tissue engineering and drug delivery. It can be difficult to manage the structure of these stimuli-responsive CS hydrogels or they may require additional crosslinking agents, such as hydrogels with dual pH and thermo-responsiveness. Therefore, it is crucial to create these hydrogels for medicinal applications.